Design of reactor for the production of zinc oxide nanoparticles - Noorlela, Anisa; Nandiyanto, Asep Bayu Dani; Ragadhita, Risti; Kurniawan, Teguh (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2023)
This study aims to design a continuous stirred tank reactor (CSTR) type reactor to produce zinc oxide (ZnO) nanoparticles. Mass balance calculations were carried out in this study as a benchmark to determine whether the reactor was working properly by knowing the flow of incoming raw materials and the products produced by the reactor. Furthermore, the reactor's design and the stirrer used in the reactor are calculated manually using Microsoft Excel. Based on the calculation results of the reactor design, the reactor volume is 8224.359 liters, with a vessel diameter of 73.298 in, a cylinder height of 166.090 in, and a cylinder thickness of 73.444 in. The top cover of the reactor measures 12.387 inches with a thickness of 0.072 inches, while the bottom cover measures 21.185 inches with a thickness of 0.083 inches, so the overall height of the reactor is 37.552 in. The reactor is equipped with one stirrer with an impeller diameter of 36.722 in, impeller height from the bottom of the tank is 24.433 in, impeller width is 7.344 in, and impeller length is 9.180 in. Turbulent stirring flow conditions with a standard motor power for the stirrer is 6.849 HP. This design will be a reference for building more economical, efficient, and highly demanding reactors.